Determining the optimal points for the construction of eco-tourism accommodation in the area of Namarstaq village using GIS - Shaqayeq Mousavi; Mahta Tari (مسکن و محیط روستا, 2023)
Nowadays, ecotourism has become an important economic activity in natural areas throughout the world, providing tourists with the opportunity to experience natural and cultural symbols and appreciate the importance of preserving biodiversity and local cultures. At the same time, this activity purpose to contribute to environmental preservation and provide economic benefits for local communities. The purpose of this study is to determine optimal locations for building an ecotourism accommodation in the village of Namarestagh, Amol. The present study is both practically and methodologically descriptive-analytical in nature, focusing on the field of urban planning. In order to achieve the research objective, information was gathered through a review of sources in the field of optimal location for ecotourism resorts, using multivariate decision-making methods and geographic information systems. Effective location criteria were identified and finalized by experts in the local tourism industry, and relevant digital maps were prepared. The final criteria used in this study include slope, vegetation cover, distance from residential areas, proximity to transportation routes, proximity to water resources, and tourism climate. Then the desired criteria were standardized and weighted using the AHP and fuzzy methods in a professional and effective manner. Ultimately, combining the layers using the WLC method resulted in a final potential map for eco-tourism accommodation development. The results of criterion weighting indicated that surface water resources, vegetation cover, transportation routes, slope, tourism climate, and habitat had the highest to lowest weights, respectively. The final results showed that seven polygons with over 70% potential were suitable for eco-tourism accommodation in the Namarestagh village. Polygon 1 had the highest potential score of 7110/0 while Polygon 6 had the lowest potential score of 6335/0. In total, 82 hectares of the studied area had a potential of over 70% for the development of eco-tourism accommodations.